Poverty in Aceh Province: The Role of Human Development, Unemployment, and Economic Growth - Hardianti, Anisha; Putri Utami, Farathika; Simanjuntak, Helmina; Sirait, Syamsinah (Lembaga Penelitian Universitas YARSI, 2026)
This study examines the effects of the Human Development Index (HDI), Open Unemployment Rate (OUR), and Gross Regional Domestic Product (GRDP) per capita on poverty in Aceh Province. Despite receiving substantial fiscal support through the Special Autonomy Fund, Aceh continues to record one of the highest poverty rates in Indonesia, indicating persistent structural challenges. This study provides district-level evidence from 23 regencies and municipalities in Aceh during 2020–2024 using panel data regression analysis. Based on the Chow, Hausman, and Lagrange Multiplier tests, the Random Effect Model was identified as the most appropriate specification. The findings reveal that HDI has a significant negative effect on poverty, indicating that improvements in education, health, and living standards contribute to poverty reduction. The Open Unemployment Rate also exhibits a significant negative relationship with poverty, suggesting the importance of regional labor market characteristics and informal employment. Meanwhile, GRDP per capita has no significant effect, implying that economic growth has not been sufficiently inclusive to alleviate poverty. These findings emphasize that strengthening human capital and improving labor market quality are more effective strategies for reducing poverty in Aceh Province.